2007
DOI: 10.1080/13854040600888784
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Parent Satisfaction with Pediatric Neuropsychological Evaluations

Abstract: Satisfaction with pediatric neuropsychological evaluations was surveyed by asking parents or guardians of children who completed pediatric neuropsychological evaluations at a large children's hospital over a 2-year period to complete a 30-item rating scale. The scale included items drawn from published measures of consumer satisfaction, and incorporated a well-validated measure of general satisfaction. A total of 338 surveys were distributed, with 117 completed, for a return rate of 35%. Respondents were gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 27 publications
7
43
2
Order By: Relevance
“…Materials consisted of a postal survey, previously used by Bodin et al (2007). Questions regarding insurance provision were not suitable for an NHS context and were removed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Materials consisted of a postal survey, previously used by Bodin et al (2007). Questions regarding insurance provision were not suitable for an NHS context and were removed.…”
Section: Methodsmentioning
confidence: 99%
“…A second study, by Bodin et al (2007) extended Farmer and Brazeal's (1998) work by combining the AIQ with the Client Satisfaction Questionnaire (CSQ-8; Attkisson and Greenfield, 2004), a standardised measure of satisfaction for which normative data are available. The combined measure was then supplemented with items from the Measure of Processes of Care (King et al, 1995) and eight novel items designed to measure aspects more relevant to their local service provision.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings provide evidence for the usefulness of information obtained from the evaluation to assist parents in advocating for services for their child, but not the usefulness of the evaluation report as a tool utilized by school practitioners to effect positive change through school programming. More recently, Bodin et al (2007) found that 43% of 117 responders reported uncertainty or disagreement with the statement, "Helped improve school services." Forty-five percent of the parents reported a perception that the evaluation did not improve their child's life.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of recommendations is to facilitate increased support for the child that includes learning advice and home based activities to improve daily-living. There is paucity in literature on parent and child satisfaction of these assessments, 5,6,7 and no identified literature on whether recommendations are implemented. 8,9 This study aimed to assess levels of satisfaction amongst parents and children with TS following neuropsychological assessment, and investigate the proportion of recommendations implemented at home and school.…”
mentioning
confidence: 99%